ERROR ANALYSIS OF BUKU INDUK BAHASA MANDARIN, SUPER KILAT KUASAI BAHASA MANDARIN - Pradono, Sudono Noto (VOCATIO : Jurnal Ilmiah Ilmu Administrasi dan Sekretari, 2018)
The purpose of this article was that the writer would like to analyze a book entitled â€œBuku Induk Bahasa Mandarin, Super Kilat Kuasai Bahasa Mandarinâ€ to know whether there were some errors or not. The writer reviewed the book, and focused on the errors in the book; he wrote each wrong sentence and classified errors based on 1. phonetic, and 2. character. The writer could conclude that the errors in â€œBuku Induk Bahasa Mandarin, Super Kilat Kuasai Bahasa Mandarinâ€ could be categorized as follows: 1) phonetics and 2) character. It seemed that the writer of â€œBuku Induk Bahasa Mandarin, Super Kilat Kuasai Bahasa Mandarinâ€ did not consult to a Chinese language dictionary when he wrote this book. Therefore, many errors could be found in this book.